Teacher education: Rationale and process; With special reference to cognitive issues - Murray, Reginald N. (Institute of Education, UWI, Mona, 1972)
This paper identifies the patterns of teacher education existing in the Caribbean, and examines the rationale and some of the more important principles on which due process should be based.
Conference on Teacher Education in the Eastern Caribbean, Basseterre, Roseau, Dominica , 10-14 April, 1972 Editor: R. M. Nicholson
Keywords: teacher education